Green InP/ZnSeS/ZnS Core Multi‐Shelled Quantum Dots Synthesized with Aminophosphine for Effective Display Applications. (20th January 2021) - Liu, Pai; Lou, Yajun; Ding, Shihao; Zhang, Wenda; Wu, Zhenghui; Yang, Hongcheng; Xu, Bing; Wang, Kai; Sun, Xiao Wei
Abstract: InP quantum dots (QDs) are emerging as promising materials for replacing cadmium‐based QDs in view of their heavy metal‐free and tunable luminescence. However, the development of InP QD materials still lags due to the expensive and flammable phosphorus precursors, and also the unsatisfactory repeatability caused by the fast nucleation rate. Adopting lowly reactive P precursor aminophosphine can overcome this issue, but their low photoluminescence quantum yield (PLQY) and widening line widths do not apply to the practical application. Through engineering, the core‐shell structure of QD, significantly promoted green emissions of QDs were obtained with PLQY of 95% and full width and half maximum (FWHM) of 45 nm, which demonstrated the highest PLQY record obtained from the aminophosphine system. Moreover, due to the residue halogen atoms on the QD surface as inorganic ligands to prevent further oxidization, these InP QDs demonstrated the ultra‐long operational lifetime (over 1000 h) for QDs based color enhancement film. By optimizing the device structure, an inverted green InP quantum dot light‐emitting diode (QLED) with external quantum efficiency (EQE) of 7.06% was also demonstrated, which showed a significant promise of these InP QDs in highly effective optoelectronic devices. Abstract : Through engineering the core‐shell structure of QD to reduce traps, significantly promoted green emissions of InP QDs with PLQY of 95% is obtained using lowly reactive P precursor aminophosphine. The outstanding photo‐ and electroluminescence devices are both presented, which are superior to those of other green‐emitting InP QDs reported in the literature.